THE MODEL OF EFFECTIVE TEAM WORK DEVELOPMENT FOR INTERNAL QUALITY ASSURANCE OF SMALL ELEMENTARY SCHOOLS IN KALASIN PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Chantarat, Pattanarin; Pumipuntu, Somjai; Tesaputa, Kowat (Journal of Buddhist Anthropology, 2022)
The objective this research were to 1) Study present conditions desirable conditions of teamwork effectiveness for internal quality assurance in small elementary schools 2) Create and develop a model of effective team work, and 3) Assessment the model of effective team work. This research is mixed methods research. Sample random sampling was collected from 185 small elementary schools by Krejcie and Morgan formular. The research tool were questionnaires, Semi-structure interview and assessment form to collect data. The statistics used for analyzing quantitative data were mean, standard deviation, and Modified Priority Needs Index (PNImodified), and content analysis was employed to analyze qualitative data and concluded in descriptive. The results of the study revealed the following: 1) Present desirable conditions and priority Needs of teamwork overall was rated in a high level. ( = 3.62, S.D. = 0.55) 2) Creating and developing a model of effective teamwork. The model consisted of 3 parts. Part 1 Introduction, consists of principles, objectives, and goals. Part 2 Content, the content is divided into: Effectiveness teamwork which are 7 components namely; communication, organizational culture, goal setting, administration, procedures and evaluation, interpersonal relationships, and leadership, Development of effectiveness teams for internal quality assurance. It consists of a six-step process: (1) Study of conditions and needs (2) Action planning (3) Plan implementation (4) Data collection and analysis (5) Evaluation and reflection (6) Improvement. Part 3 The model Implementation, approaches for enhancement of teamwork effectiveness and condition. 3) The assessment of effective teamwork development model. overall, the appropriateness ( = 4.90, S.D. = 0.19) feasibility ( = 4.85, S.D. = 0.30) and the usefulness ( = 4.93, S.D. = 0.14) of the model were rated at the highest level.